Development of peer tutoring-based training to improve elementary school teacher competence in making merdeka curriculum lesson plans - Laksmi, Javid Nama Ayu; Mawardi, Mawardi; Wasitohadi, Wasitohadi (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
The previous study shows teachers' pedagogical competence in making lesson plans is still low, especially in making Merdeka Curriculum lesson plans. The training that has been developed is inadequate for this need. This study aims to develop a peer tutoring-based training design to improve teachers' pedagogical skills in making Merdeka Curriculum lesson plans. The type of research used in this research is R&D and the product was developed by Dick & Carey model. The method used in this research is a combination of quantitative and qualitative methods. The sampling technique used is simple random sampling. The research subjects were 16 fifth-grade teachers in Pabelan District, Semarang Regency. Data collection techniques included open-ended questionnaires, pretest, and posttest instruments. Quantitative data analysis used category description and the Wilcoxon test. The finding of research results showed that peer tutoring-based training design that has been developed is conducted with guidance in small groups, in contrast to previous training that was conducted in a classical. This design has been validated by the experts and has been revised based on their suggestions. The product trial results show the effectiveness of peer tutoring training design in improving teachers’ pedagogical competence in making Merdeka Curriculum lesson plans. Therefore, this training design could be used in the next product trial. It can also be applied to teacher training programs to improve teacher's ability to make lesson plans.